Tanggung Jawab Hukum Penilai Publik terhadap Laporan Penilaian Kegiatan Pengadaan Tanah bagi Pembangunan untuk Kepentingan Umum (Studi Atas Kantor Jasa Penilai Publik Toto Suharto) - Gagah Yaumiyya Riyoprakoso; AM Hasan Ali; Fitriyani Zein (JOURNAL of LEGAL RESEARCH, 2020)
This study is based on the legal responsibility of the assessment of public appraisal reports they make in land procurement activities for development in the public interest. Public assessment is obliged to always be accountable for their assessment. The type of research found in this thesis is a type of normative legal research with the right-hand of the statue approach and case approach. Normative legal research is a study that provides systematic explanation of rules governing a certain legal category, analyzing the relationship between regulations explaining areas of difficulty and possibly predicting future development. . After conducting research, researchers found that one of the causes that made the dispute was a lack of communication conducted between the Government and the landlord. In deliberation which should be the place where the parties find the meeting point between the parties on the magnitude of the damages that will be given, in the field is often used only for the delivery of the assessment of the compensation that has been done.